Identification and analysis of major flavor compounds in radish taproots by widely targeted metabolomics - Mei, Shiyong; He, Zhengjin; Zhang, Jifang (Frontiers in Nutrition, 2022)
Radish (Raphanus sativus L.) is an important Brassicaceous vegetable crop that is cultivated worldwide. The taste of radish can be described as pungent, sweet, and crisp. At present, the metabolic characteristics leading to differences in radish taste remain unclear, due to the lack of large-scale detection and identification of radish metabolites. In this study, UPLC-MS/MS-based targeted metabolome analysis was performed on the taproots of eight radish landraces. We identified a total of 938 metabolites, and each landrace exhibited a specific metabolic profile, making it unique in flavor and quality. Our results show that taste differences among the taproots of different radish landraces can be explained by changes in composition and abundance of glucosinolates, polyphenols, carbohydrates, organic acids, amino acids, vitamins, and lipids. This study reveals the potential metabolic causes of variation in the taste and flavor of radish taproots.